Kajian Pustaka tentang Efektivitas Manajemen Pelayanan Posyandu dalam Meningkatkan Kepuasan Masyarakat - Dwi Laelani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Integrated Service Posts (Posyandu) play a strategic role in improving maternal and child health in Indonesia thru community empowerment. However, the effectiveness of Posyandu service management still faces various challenges, such as service quality, cadre empowerment, and technology utilization. This study uses a Systematic Literature Review (SLR) approach based on PRISMA and Kitchenham & Charters to analyze patterns and trends in Posyandu service management and the factors influencing its effectiveness, based on the latest scientific literature. The literature review integrates Human Resource Management theory, Total Quality Management, and the SERVQUAL model to analyze the input-process-outcome relationship in community services. The literature search was conducted systematically on indexed databases (Sinta, Scopus, DOAJ) for publications between 2022 and 2025, applying inclusion-exclusion criteria and a phased screening process. The final sample consisted of 12 articles analyzed thru full-text extraction and documentation of the PRISMA selection flow. The research findings indicate that the effectiveness of Posyandu service management is significantly influenced by several factors, such as the competence and empowerment of volunteers, consistent implementation of work procedures, the use of digital technology, and socio-geographic factors that moderate service delivery. This finding also reveals differences in effectiveness between Posyandu in urban and rural areas, particularly in addressing health issues such as stunting. It is recommended to strengthen cadre training, implement more consistent work procedures, and utilize technology to improve the efficiency and quality of Posyandu services in order to increase community participation and satisfaction.